The Effect of Fraction Adventure Gamification Media in Improving Fraction Calculation Operation Skills and Learning Motivation of Phase C Students - Wibowo, Ayu Radiandara; Gunarhadi, Gunarhadi; Karsono, Karsono (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
This study aims to examine the effect of Fraction Adventure gamification media on fraction calculation operation skills and learning motivation of Phase C elementary school students. The research method used was quantitative with a 2x2 factorial pseudo-experimental design. This study involved 102 students from four elementary schools in Selogiri District, Wonogiri, who were grouped into experimental and control classes. The experimental class used Fraction Adventure gamification media, while the control class used a quartet card game. Data were collected through a fraction calculation skill test and a learning motivation questionnaire. The results of the analysis showed that there was a significant effect between learning motivation and fraction calculation operation skills. However, Fraction Adventure media directly had no significant effect when viewed separately from student motivation. This finding suggests that Fraction Adventure media is more effective on students with high learning motivation. The conclusion of the study confirms the importance of considering students' characteristics in choosing learning strategies, as well as the potential development of Fraction Adventure to support mathematics learning.